FACTOR ANALYSIS OF PUSH AND PULL TRAVEL MOTIVATION OF FOREIGN TOURISTS TO LOMBOK - Made Padmi Shantika (Perpustakaan Universitas Surabaya, 2014)
The role of tourism sector in economy is undeniable. It gives a contribution to national GDP and opens job opportunities for people in its related sectors. The potential of tourism in the country are numerous and need to be developed in order to maximize its contribution to the country. Tourism is growing in some provinces in the country and it draws attention to study it. This is a descriptive research which used a quantitative approach. This research is aimed to identify the push and pull travel motivation of foreign tourists in visiting Lombok, therefore this research adopts a model based on push and pull factors as the conceptual framework. As information has been documented about push and pull travel motivations to Lombok and factor analysis has been done for analyzing the data which may have important marketing implications to the business owners and government.